Response of promiscuous soybean to rhizobial inoculation in combination with organic and mineral fertilizers in some soils of the Nigeria Guinea Savanna - Ekaette, J.E. (Federal University of Technology Minna, 2017)
Effective soybean rhizobia are seldom found in sufficient or large numbers in the soils that have no history of soybean cultivation. There may be a need for soybean grown in such soils to be supplied with inoculant rhizobia to ensure optimal inputs from biological nitrogen fixation. Reports have indicated that yield per hectare of soybean in farmers’ fields are still very low. This scenario calls for trials that are capable of establishing some of the biophysical factors limiting the yield of soybean in Nigerian savannas. Available information in literature showed that in addition to the deficiencies of N, P and to some extent potassium, there are generally low to deficient levels of Cu, Mo and Zn in a number of soils from Nigerian savanna. Also, the organic matter content in these soils is low, thus there is need to add organic manure in order to raise the fertility thereby improving soil physical, chemical and biological properties. A trial was set up to diagnose the underlying factors responsible for variation in yield among soybean treatments at four sites in Shiroro Local Government Area of Niger State. The trial consisted of six (6) treatments in the first year, nine (9) treatments in the second year replicated four (4) times arranged in randomized complete block design (RCBD). The treatments were (i) Control, (ii) Inoculant only, (iii) Inoculant + phosphorus (30kg P2O5/ha), (iv) Inoculant + phosphorus + potassium (20kg K2O/ha), (v) Inoculant + phosphorus + potassium + micronutrients (3.3kg/ha) and (vi) Inoculant + phosphorus + potassium + micronutrients + organic manure (4tons/ha), (vii) Inoculant + organic manure, (viii) Inoculant +phosphorus + micronutrient and (ix) Organic manure only. Response to nutrients varied across sites. Treatments with organic matter were significantly greater than the control in terms of plant height, nodule number and shoot dry weight but marginally greater than the control in pod number and pod dry weight. The treatments with inoculant only had similar yield parameters as the control in terms of plant height, shoot biomass, days to 50% flowering, nodule number /weight, pods per plant, number of seeds per pod, grain yield and stover yield, also treatment with inoculant only had similar yield parameters as the mineral fertilizer treatments in terms of plant height @ 4WAS in both year, nodule number, nodule weight, number of branches, days to 50% flowering and stover yield as well as the organic matter treatments. The results indicate the benefit of using bio, mineral and organic fertilizers in improving the productivity of soybean.